Decellularization of xenografted tumors provides cell-specific in vitro 3D environment - Iazzolino, Gaia; Mendibil, Unai; Arnaiz, Blanca; Ruiz-de-Angulo, Ane; Azkargorta, Mikel; Uribe, Kepa B.; Khatami, Neda; Elortza, Felix; Olalde, Beatriz; Gomez-Vallejo, Vanessa; Llop, Jordi; Abarrategi, Ander (Frontiers in Oncology, 2022)
In vitro cell culture studies are common in cancer research field, and reliable biomimetic 3D models are needed to ensure physiological relevance. In this manuscript, we hypothesized that decellularized xenograft tumors can serve as an optimal 3D substrate to generate a top-down approach for in vitro tumor modeling. Multiple tumor cell lines were xenografted and the formed solid tumors were recovered for their decellularization by several techniques and further characterization by histology and proteomics techniques. Selected decellularized tumor xenograft samples were seeded with HCC1806 human triple negative breast cancer (TNBC) basal-like subtype cell line and cell behavior was compared among them and with other control 2D and 3D cell culture methods. A soft treatment using Freeze-EDTA-DNAse allows proper decellularization of xenografted tumor samples. Interestingly, proteomic data show that samples decellularized from TMBC basal-like subtype xenograft models had different extracellular matrix (ECM) composition compared to the rest of xenograft tumors tested. The in vitro recellularization of decellularized ECM (dECM) yields tumor-type specific cell-behavior in TNBC context. Data indicate that dECM derived from xenograft tumors is a feasible substrate for reseeding purposes, thereby promoting tumor-type specific cell behavior. These data serve as a proof-of-concept for further potential generation of patient-specific in vitro research models